Cold pressor test in diagnosis of coronary artery disease: echophonocardiographic method. Issue 6382 (18th June 1983) - Seneviratne, B I; Linton, I; Wilkinson, R; Rowe, W; Spice, M
Abstract : The cold pressor test was used to induce myocardial ischaemia in patients with coronary artery disease and the rise in left ventricular filling pressure used as the index of myocardial ischaemia. Left ventricular filling pressure was derived from a non-invasive echophonocardiographic method. A study group of 19 consecutive patients with chest pain underwent the cold pressor test before coronary angiography. Eighteen responded with a rise in filling pressure exceeding 30% and, of these, 17 had serious coronary artery disease (three single vessel, one two vessel, and 13 triple vessel disease; one had coronary artery spasm only). The remaining patient, who showed no rise in filling pressure, did not have coronary artery disease. None of 15 normal controls showed a rise greater than 5% (patients with coronary artery disease versus normal controls p less than 0.001). The cold pressor test would be suitable for patients who cannot or should not exercise and may be combined with exercise electrocardiograms to improve the information content, as it uses a different marker of myocardial ischaemia.